Nitrogen and sulfur doped mesoporous carbon as metal-free electrocatalysts for the in situ production of hydrogen peroxide. (December 2015) - Perazzolo, Valentina; Durante, Christian; Pilot, Roberto; Paduano, Andrea; Zheng, Jian; Rizzi, Gian Andrea; Martucci, Alessandro; Granozzi, Gaetano; Gennaro, Armando
Abstract: Mesoporous carbons (MCs) are highly porous materials, which offer high surface area and higher electrochemical performance than traditional carbon materials. Doped carbons are particularly interesting materials due to their possible use as metal-free ORR catalysts. In this paper, nitrogen and sulfur doped or co-doped MCs were prepared according to a hard template approach consisting in pyrolysis of powders obtained by liquid impregnation of mesoporous silica with different heterocyclic condensed aromatic precursors. The synthetized MCs show round shaped particles with mesoporosity of 3–4 nm diameter, a BET surface area higher than 850 m 2 /g and nitrogen and sulfur contents ranging between 3–8% and 4–14%, respectively. Final doping has been demonstrated by core level photoemission spectra. The effect of the pyrolysis temperature on the physico-chemical properties of the resulting MCs has been investigated as well as the role of the dopant heteroatoms on their catalytic performances towards oxygen reduction reaction (ORR). Electrochemical tests show that both the oxygen-, sulfur- and nitrogen-containing groups can induce an electrocatalytic activity of MCs for ORR. The catalytic activity shows a linear dependence from the nitrogen content and a prevalent 2 electron reduction process leading to the formation of hydrogen peroxide, both in acid and alkaline solution.